A blue to red light sensitive photoinitiating systems based on 3, 5-di-tert-butyl-o-benzoquinone derivatives for free radical polymerization. (15th March 2020) - Shurygina, Margarita P.; Zakharina, Maria Yu.; Baten'kin, Maxim A.; Konev, Alexey N.; Shavyrin, Andrey S.; Chelnokov, Egor A.; Shushunova, Nataliya Yu.; Arsenyev, Maxim V.; Chesnokov, Sergey A.; Abakumov, Gleb A.
Graphical abstract: Highlights: New well-photobleachable initiating systems based on unsubstituted and four 6-CH2 X-substituted 3, 5-di- tert -butyl- o -benzoquinones and tertiary amines were used for deep (up to 46 cm) photocuring methacrylic resins under visible light irradiation. Abstract: New well-photobleachable initiating systems based on unsubstituted and four 6-CH2 X-substituted 3, 5-di- tert -butyl- o -benzoquinones (X = H, OCH3, dimethylpyrazole and benzimidazole fragments) and tertiary amines were used for photocuring different methacrylic resins under visible light irradiation. A photoreduction of these o -quinones in the presence of a series of N, N-dimethylanilines under of visible irradiation was studied. Photoinitiating properties of this series of o -benzoquinones in the presence of N, N-dimethylaniline were investigated on the example of the curing resin based on triethylene glycol dimethacrylate (TEGDMA). The photoinitiation system based on o -quinone with dimethylpyrazole fragment and N, N-dimethylaniline has the highest efficiency in this series. It was shown that the use of this initiating system allows to photocure thick layers of TEGDMA/bis-GMA (30/70 wt%) resin (0.5 cm) under the action of both LEDs with λmax 465, 520 and 630 nm. A deep photopolymerization of the composition layer (46 cm thickness) under radiation of LED@600 nm (540 mW cm −2 ) was carried out. The average speed of the front of photopolymerization is 2.56 cm/min.